Da fala para a escrita : uma abordagem da monotongação e da ditongação na escrita - Silva, Karine Melo e (2015)
This study develops an analysis of the phenomena of monophthongization and diphthongization in writing. In speech, these phenomena occur systematically and do not imply any social assessment. However, when we transpose for writing, they result in misspellings, which act as a source of censorship and discrimination. Given these considerations, we produce educational material in order to contribute to erasing the monophthongization and diphthongization in writing, since it is in this type of language that these phenomena are stigmatized. The proposed Didactic Module is the result of application of a sequence of activities that promote constant writing of favoring words of monophthongization and diphthongization, to contribute to the filed of spelling, through by deleting these phenomena. Its structure is divided into three sections. Initially, there is the issue with theoretical foundation in order to clarify concepts and reflections about the studied phenomena. Then we have a practice section, in which the developed activities are described. These activities are like crosswords, word search and work with text, through different stimuli, which, establishing the speech writing seek to contribute to the progressive deletion of monophthongization and diphthongization in writing. Finally, we bring the final consideration, with reflections on the sequence of developed activities and with indications of further readings and of other materials that greatly contributed to this study. This module was conducted for five classes, in a sixth grade class of Elementary School of the State High School 24 de Outubro (Aracaju/SE). Our theorical framework are Mollica (1998;2003), Bortoni-Ricardo (2004), Morais (2006), Cagliari (2007), Hora (2009) e Seara;Nunes; Lazzarotto-Volcãos´s (2011) studies, among other that were focused on the studied aspects here. We could verify, through the obtained data, that the developed activities have contributed to the treatment of the studied phenomena, since students showed a progressive deletion of monophthongization and diphthongization in writing. So we understand the importance of this Didactic Module not only because it is a specific teaching materials for these phenomena treatments, but also to present a differentiated approach to orthography, with recreational activities and work with texts, assisting the teacher to develop a systematic and effective education of the orthographic norms.